Fluid management concepts for severe neurological illness: an overview. Issue 5 (October 2018) - Heifets, Boris D.; Tanaka, Pedro; Burbridge, Mark A.
Abstract : Purpose of review: The acute care of a patient with severe neurological injury is organized around one relatively straightforward goal: avoid brain ischemia. A coherent strategy for fluid management in these patients has been particularly elusive, and a well considered fluid management strategy is essential for patients with critical neurological illness. Recent findings: In this review, several gaps in our collective knowledge are summarized, including a rigorous definition of volume status that can be practically measured; an understanding of how electrolyte derangements interact with therapy; a measurable endpoint against which we can titrate our patients' fluid balance; and agreement on the composition of fluid we should give in various clinical contexts. Summary: As the possibility grows closer that we can monitor the physiological parameters with direct relevance for neurological outcomes and the various complications associated with neurocritical illness, we may finally move away from static therapy recommendations, and toward individualized, precise therapy. Although we believe therapy should ultimately be individualized rather than standardized, it is clear that the monitoring tools and analytical methods used ought to be standardized to facilitate appropriately powered, prospective clinical outcome trials.